2015
DOI: 10.1002/app.43059
|View full text |Cite
|
Sign up to set email alerts
|

Modulating stability and mechanical properties of silica–gelatin hybrid by incorporating epoxy‐terminated polydimethylsiloxane oligomer

Abstract: ABSTRACT:Silica-gelatin hybrids, particularly GT-G hybrids prepared by crosslinking gelatin (G) with cglycidoxypropyltrimethoxysilane (GT), have attracted much attention in tissue engineering for diverse applications in hard or soft tissue regeneration; however, scaffolds with tunable properties are needed to meet specific requirements. In this work, a silica-gelatin hybrid (ES/GT-G) was synthesized by incorporating epoxy-terminated polydimethylsiloxane oligomer (ES) to modulate the properties of GT-G hybrid. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 33 publications
0
20
0
1
Order By: Relevance
“…Total porosity of the sample was determined according to the liquid displacement method . And the detailed determination was shown in Supporting Material S4.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total porosity of the sample was determined according to the liquid displacement method . And the detailed determination was shown in Supporting Material S4.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, gelatin (GE), a biodegradable polymer derived from collagen, has been widely used in many fields including tissue regeneration, food industry, cosmetic, and targeted drug delivery, due to its excellent solubility, low toxicity, good bioresorbability, favorable degradability, easy to be modified, and so on . With respect to silica‐GE hybrid materials, our group found incorporation of epoxy‐terminated polydimethylsiloxane oligomer could enhance its thermal stability, flexibility, and biodegradability, and revealed that the in vitro degradation behavior could be modulated by controlling the dosage of silica‐containing component .…”
Section: Introductionmentioning
confidence: 99%
“…Аналіз літературних джерел інформації свідчить про можливість використання сполук кремнію в процесі дублення шкіряного напівфабрикату. Так, у [3], в результаті дослідження впливу гліцидоксипропілтриметокси-сілану та сумісно з епоксиполідіметилсілоксановим олігомерам і 1,5% сполуками хрому основністю 33% на структурні властивості козлини встановлено, що зі збільшенням витрат сполук органосілікону підвищується пористість шкіряного напівфабрикату та його гідротермічна стійкість. Додаткове застосування сполук хрому з органосіліконом сприяє підвищенню цих показників.…”
Section: застосування нано-Sio 2 в технології виробництва еластичних unclassified
“…However, poor mechanical strength, high hydrophilicity and rapid degradability greatly limit its effective and wide application . Our previous studies demonstrated that the incorporation of polydimethylsiloxane (PDMS) chains in GE molecules could improve the mechanical flexibility, porous structure and degradation resistance, but the proposed GE‐based materials are simply designed as a single‐layer film . In contrast, silicone rubber (SR), a typical synthetic material, has inherent hydrophobicity, high flexibility and good biocompatibility but poor biodegradability .…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Our previous studies demonstrated that the incorporation of polydimethylsiloxane (PDMS) chains in GE molecules could improve the mechanical flexibility, porous structure and degradation resistance, but the proposed GE-based materials are simply designed as a single-layer www.soci.org W Du, Z Zhang, Z Li film. [17][18][19] In contrast, silicone rubber (SR), a typical synthetic material, has inherent hydrophobicity, high flexibility and good biocompatibility but poor biodegradability. 20,21 As known from the self-stratification strategy, the combination of GE or modified GE and SR is a feasible approach to fabricate a porous bilayer membrane, thus expressing their respective advantages.…”
Section: Introductionmentioning
confidence: 99%